Cambridge O level Mathematics coursebook - Saya, Ahmed; Chalmers, Dean (UK : Cambridge university press, 2023)
Cambridge O Level Mathematics provides comprehensive coverage of the O Level Mathematics syllabus, offering clear explanations, worked examples, and practice exercises across core and extended topics. Authored by experienced educators Ahmed Saya and Dean Chalmers, the book builds problem-solving skills and mathematical reasoning through step-by-step guidance and exam-style questions, helping students prepare effectively for assessments.
Keywords: Mathematics - Text Book